TEORI PERSEPSI MULLÃ SHADRÃ BESERTA IMPLIKASI EPISTEMOLOGI DAN METODOLOGISNYA UNTUK PSIKOLOGI - Heriyanto, Husein (Jurnal Studia Insania, 2015)
Human action is seen as behavior of organisms that are subject to the law of effect (the law of effect) throughÂ the process of reinforcement and punishment, stimulus-response mechanism, learning by trial, and the laws ofÂ Biochemistry and physiological. MullÃ¢ ShadrÃ¢ has brought us to a new consciousness that we are over this as ifÂ asleep because it doesnât realize that all our actions including sensory perception is our soulâs activity directly.Â Epistemolois and methodological implications of the theory of perception ShadrÃ¢ this potentially to do aÂ revolution in psychology, that relives live, i.e. as a single agent â holistic in all the actions of our perception andÂ cognition